2015
DOI: 10.1016/j.ijrobp.2015.08.003
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Value of Plasma Epstein-Barr Viral DNA and Tumor Response to Neoadjuvant Chemotherapy in Advanced-Stage Nasopharyngeal Carcinoma

Abstract: Detectable EBV DNA levels and an unsatisfactory tumor response (stable disease or disease progression) after NACT serve as predictors of poor prognosis for patients with advanced-stage NPC. These findings will facilitate further risk stratification, early treatment modification, or both before CCRT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
105
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 123 publications
(123 citation statements)
references
References 33 publications
17
105
0
1
Order By: Relevance
“…Age, smoking history, EBV-DNA load, HB, GTVnx, and T and N classification as well as clinical stage have been reported to have a prognostic role in primary NPC patients in previous studies5254555657. In our study, age 50 was chosen to be the cut-off value according to previous studies on NPC patients as reported by Chen et al 54…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Age, smoking history, EBV-DNA load, HB, GTVnx, and T and N classification as well as clinical stage have been reported to have a prognostic role in primary NPC patients in previous studies5254555657. In our study, age 50 was chosen to be the cut-off value according to previous studies on NPC patients as reported by Chen et al 54…”
Section: Discussionmentioning
confidence: 98%
“…P values were marked as *P < 0.05, **P < 0.01, ***P < 0.001, indicating different level of significance. These statistical analyses were performed with SPSS 16.0 484950515253545556575859.…”
Section: Methodsmentioning
confidence: 99%
“…In our study, 9% of patients had stable disease after three cycles of TPF IC. Liu et al [17] found that an unsatisfactory tumor response (stable disease or disease progression) or detectable EBV DNA levels after IC were predictors of poor prognosis for patients with locoregionally advanced NPC. In a prospective study of children and young adults with NPC, the radiation dose during CCRT was decreased to 54 Gy in patients who achieved complete remission and 59.4 Gy in those who achieved partial remission after three cycles of IC; after a median follow-up of 30 months, none of these patients experienced locoregional recurrence [18].…”
Section: Main Textmentioning
confidence: 99%
“…Liu and al. revealed that the unsatisfactory tumor response after induction chemotherapy (stable disease or disease progression) could predict poor prognosis for patients with advanced-stage NPC (locoregional relapse-free survival,PFS) [23]. However ;an another trial concluded that the overall tumor response after induction chemotherapy was an independent prognostic factor for disease-free-survival , OS and locoregional recurrence free survival [24].…”
Section: Resultsmentioning
confidence: 99%